2013
DOI: 10.1515/jpm-2012-0252
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR C677T polymorphism, folate, vitamin B12 and homocysteine in recurrent pregnancy losses: a case control study among north Indian women

Abstract: Low vitamin B₁₂ increases homocysteine, specifically among T allele carrying case mothers, suggesting T allele is detrimental with B₁₂ deficiency. The study emphasizes the importance of vitamin B₁₂ in the prevention of RPL in North Indian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
31
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 5 publications
8
31
0
2
Order By: Relevance
“…In our study, the frequency of genetic polymorphisms that encode enzymes involved in folate-and vitamin B12-dependent homocysteine metabolism, the MTHFR C677T and A1298C; MS A2756G and CBS 844ins68 insertion, did not show differences in a group of women with recurrent miscarriage and a control group. This is in agreement with Puri et al 15 and Zonouzi et al that investigated the MTHFR polymorphisms in North India and Iran respectively. In contrast, other studies described the relationship between the gene polymorphisms: MTHFR 4,20 ; MS 26 and recurrent abortion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, the frequency of genetic polymorphisms that encode enzymes involved in folate-and vitamin B12-dependent homocysteine metabolism, the MTHFR C677T and A1298C; MS A2756G and CBS 844ins68 insertion, did not show differences in a group of women with recurrent miscarriage and a control group. This is in agreement with Puri et al 15 and Zonouzi et al that investigated the MTHFR polymorphisms in North India and Iran respectively. In contrast, other studies described the relationship between the gene polymorphisms: MTHFR 4,20 ; MS 26 and recurrent abortion.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies had demonstrated a higher frequency of homozygous to the MTHFR C677T genotype and higher tHcy serum levels in women with recurrent miscarriage than in control groups 15,22 . However, Creus et al 6 and Pihusch et al 25 did not demonstrate such association.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…; Puri et al . ). In relation to cognitive outcomes in children, several studies did not find an association between maternal tHcy levels and cognitive measures (Tamura et al .…”
Section: Discussionmentioning
confidence: 97%
“…Elevated levels of homocysteine have been associated with many diseases, such as neurodegenerative disorders, recurrent pregnancy loss, neural tube defects, ischemic heart disease and stroke, atherosclerosis, and congenital defects [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34]. Our study shows that the MTRR rs326119 polymorphism is associated with levels of plasma homocysteine.…”
Section: Discussionmentioning
confidence: 70%